New-Onset Atrial Fibrillation in St-Segment Elevation Myocardial Infarction: Predictors and Impact on Therapy And Mortality - Congo,Kisa Hyde (2019)
Abstract Backgrund: New-onset atrial fibrillation complicating acute myocardial infarction represents an important challenge, with prognostic significance. Objective: To study the incidence, impact on therapy and mortality, and to identify predictors of development of new-onset atrial fibrillation during hospital stay for ST-segment elevation myocardial infarction. Methods: We studied all patients with ST-elevation myocardial infarction included consecutively, between 2010 and 2017, in a Portuguese national registry and compared two groups: 1 - no atrial fibrillation and 2 - new-onset atrial fibrillation. We adjusted a logistic regression model data analysis to assess the impact of new-onset atrial fibrillation on in-hospital mortality and to identify independent predictors of its development. A p value < 0.05 was considered significant. Results: We studied 6325 patients, and new-onset atrial fibrillation was found in 365 (5.8%). Reperfusion was successfully accomplished in both groups with no difference regarding type of reperfusion. In group 2, therapy with beta-blockers and angiotensin-conversion enzyme (ACE) inhibitors/angiotensin receptor blockers (ARBs) was less frequent, 20.6% received anticoagulation at discharge and 16.1% were on triple therapy. New-onset atrial fibrillation was associated with more in-hospital complications and mortality. However, it was not found as an independent predictor of in-hospital mortality. We identified age, prior stroke, inferior myocardial infarction and complete atrioventricular block as independent predictors of new-onset atrial fibrillation. Conclusion: New-onset atrial fibrillation remains a frequent complication of myocardial infarction and is associated with higher rate of complications and in-hospital mortality. Age, prior stroke, inferior myocardial infarction and complete atrioventricular block were independent predictors of new onset atrial fibrillation. Only 36.7% of the patients received anticoagulation at discharge.